2021
DOI: 10.1097/aco.0000000000000991
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric obesity and perioperative medicine

Abstract: Purpose of reviewChildhood obesity is a public health emergency that has reached a pandemic level and imposed a massive economic burden on healthcare systems. Our objective was to provide an update on (1) challenges of obesity definition and classification in the perioperative setting, (2) challenges of perioperative patient positioning and vascular access, (3) perioperative implications of childhood obesity, (3) anesthetic medication dosing and opioid-sparing techniques in obese children, and (4) research gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Nonetheless, regardless of the care setting, the observations from these earlier studies are commonly used in making recommendations for the perioperative care of children with obesity. 17 Very few studies have examined the prevalence of obesity in a pediatric ambulatory surgical population, 18 and no pediatric study to date has described obesity trends or the association of obesity with hospital admission following ambulatory surgery. Recent data from adults have yielded conflicting results on the outcome of morbidly obese patients who underwent ambulatory surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, regardless of the care setting, the observations from these earlier studies are commonly used in making recommendations for the perioperative care of children with obesity. 17 Very few studies have examined the prevalence of obesity in a pediatric ambulatory surgical population, 18 and no pediatric study to date has described obesity trends or the association of obesity with hospital admission following ambulatory surgery. Recent data from adults have yielded conflicting results on the outcome of morbidly obese patients who underwent ambulatory surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These earlier studies have typically treated children with obesity as a homogenous group. Nonetheless, regardless of the care setting, the observations from these earlier studies are commonly used in making recommendations for the perioperative care of children with obesity 17 …”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases perioperative respiratory adverse events [7 ▪ ,19] as well as the likelihood of unanticipated admission [7 ▪ ,22 ▪▪ ]. A recent study of the National Surgical Quality Improvement Program-Pediatric (NSQIP-P) database by Tram et al [22 ▪▪ ] found higher rates of same day hospital admission following elective ambulatory surgery in children with severe (Class 2/3) obesity compared to healthy weight children.…”
Section: Obesitymentioning
confidence: 99%
“…They may also fail to appreciate the increased perioperative risks certain pediatric comorbidities lend. This can lead to a false sense of security and lack of preparedness, which may result in failure to rescue [7 ▪ ]. The ability to intervene early to avert a crisis is influenced by both institutional and provider experience and preparedness [8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in the anesthesia literature suggest that children with obesity are more likely to experience intraoperative adverse events, including airway obstruction and oxygen desaturations, than their healthyweighted peers. [8][9][10][11][12][13][14][15] It remains unclear whether these observations extend to all surgical interventions, or whether there are specific BMI limits above which standard pediatric anesthesia protocols should be adapted. In contrast, there are several recent studies that suggest the majority of children with obesity complete surgical treatment without experiencing adverse events.…”
Section: Introductionmentioning
confidence: 99%